Experimental and Numerical Study on the Anchorage Effect of Bolted Jointed Rock Masses - Yang, Zhen; Zhu, Wancheng; Guan, Kai; Yan, Baoxu; Luo, Wenjun; Liang, Peng (Frontiers in Earth Science, 2022)
Anchor technology has become an irreplaceable geotechnical engineering reinforcement measure. To clarify anchorage effects and investigate the three-dimensional (3D) crack propagation process of bolted jointed rock masses, a series of physical model tests and 3D numerical simulations were performed, and optimal anchoring conditions of jointed rock masses are found. The results showed that a bolted jointed rock mass had stronger compressive performance and deformation capability, with crack propagation controlled, especially in the anchorage zone, and the formation and slip of shear zones also restrained. Meanwhile, the fractured location is transferred from the joint tip to the interface between the bolt and surrounding rock. The numerical simulation based on the damage model of rocks at the mesoscale and a nonlinear shearing–sliding model for anchoring interfaces were conducted with the FLAC3D code to reproduce the 3D crack propagation and the gradual damage of bolted jointed rock masses. The anchorage effect increased the crack initiation stress of jointed rock masses, but the zone where the bolt passed through the joint cracked more easily. Once onset of the instability stage of the bolted jointed rock mass, cracks began to propagate and penetrate gradually to the anchorage zone. In addition, under uniaxial compression, a “Z”-shaped shear stress concentration zone is observed in the bolt, which is mainly attributed to the role of the bolt on controlling shear failure along the joint plane and transverse dilatancy of the specimen. Better anchorage effects were achieved by installing bolts after deformation of the jointed rock mass had developed to a certain extent. The optimal anchor opportunity for a jointed rock mass varied with the joint angle. More specifically, for the rock mass with a joint angle of 75°, the anchorage effect was best when the bolt was installed at 40% peak strain of the jointed rock mass, while 10% peak strain was perfect for the bolted rock mass with a 45° joint angle.